2014
DOI: 10.1007/s13224-014-0592-6
|View full text |Cite
|
Sign up to set email alerts
|

A New Maneuver for Prevention of Postpartum Haemorrhage

Abstract: Background Postpartum hemorrhage (PPH) is the leading cause of maternal mortality worldwide. Many methods have been developed to decrease its rate. The aim of this study was to evaluate the applicability of a new nonpharmacologic maneuver in decreasing its rate. Methods This case series study was conducted in one center in Cairo, Egypt, from January-2010 to June-2013. 400 pregnant women, aged 18 years or more and candidate for normal labor, were enrolled to this study. High risk subjects for PPH were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Amr H et al, conducted a similar study in Egypt on 400 participants and showed reduced amount of blood loss and reduced incidence of PPH. 6 Our results were also similar to the results of a study conducted in India that reported a decrease in mean blood loss with the use of cervical traction method. 7 Along with AMTSL, the cervical traction has significantly reduced blood loss after delivery, but the difference in the incidence of PPH was insignificant in groups because of the small sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Amr H et al, conducted a similar study in Egypt on 400 participants and showed reduced amount of blood loss and reduced incidence of PPH. 6 Our results were also similar to the results of a study conducted in India that reported a decrease in mean blood loss with the use of cervical traction method. 7 Along with AMTSL, the cervical traction has significantly reduced blood loss after delivery, but the difference in the incidence of PPH was insignificant in groups because of the small sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Three studies have reported on the use of Amr's maneuver: a case‐series study by the maneuver's creator, a nonrandomized comparative study with a sample size of 200 women, and a randomized controlled study that recruited 500 women . Both comparative studies used the blood collecting drape method to estimate blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Hamdy described a new maneuver (Amr's maneuver) for the prevention of PPH, which applied sustained cervical traction after placental delivery. 11 The aim of the present multicenter randomized controlled trial was to test the hypothesis that using Amr's maneuver in conjunction with AMTSL would decrease the incidence of PPH after vaginal delivery more than that achieved by AMTSL alone, and reduce the amount of blood loss.…”
Section: Confederation Of Midwives and The International Federation Ofmentioning
confidence: 99%
“…In the last two decades, many efforts and researches were conducted to improve the preventive measures for PPH which finalized in 2012 by the addition of misoprostol as an alternative for oxytocin [11] . In 2014, Hamdy Amr described his new maneuver by applying the sustained cervical traction for the prevention of PPH [12] . In addition, his maneuver proved effective when added to AMSTL in reduction of the amount of postpartum blood loss [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Hamdy Amr described his new maneuver by applying the sustained cervical traction for the prevention of PPH [12] . In addition, his maneuver proved effective when added to AMSTL in reduction of the amount of postpartum blood loss [12][13][14][15] . Thus, the rationale intended for this current randomized controlled trial was to measure the effects of Amr' Maneuver on the uterine artery hemodynamics indices.…”
Section: Introductionmentioning
confidence: 99%